Leading Tomorrow How Effective Leaders Change Paradigms, Build Responsible Brands, and Transform Employees. - Aseervatham, Raj. (Milton : Productivity Press, 2021)
Maintaining good business leadership in a world of rapidly changing expectations levied by customers, investors, society, governments and employees is a challenge. These stakeholders are increasingly making choices about if or how they support businesses - through the purchase of their products and services, shareholdings and financing, regulatory approvals, and even experiences working for them - based on not just what a business does, but how it does it. We are seeing shifts in stakeholder sentiments that manifest in a greater expectation that businesses work with society in addressing society's contemporary concerns. This greater good that businesses bring is rewarded by a greater brand awareness, connection and loyalty, which in turn provides businesses with an underlying strategic advantage over the competition with its customers, investors and other stakeholders. But this greater good cannot be faked with PR and bought media; in an increasingly connected world populated by an increasingly savvy millennial stakeholder base, authentic leadership and its ability to effect cultural shifts in the DNA of businesses is essential. Failure to do so will likely result in shorter and less successful tenures of Board members and C-suite leaders as this business trend spreads. This book looks at how the emerging generation of leaders must change paradigms and transform their employees to do more than just operate a business. It examines how to effect culture shifts that are necessary to innovate businesses so that they simultaneously meet market needs while meeting stakeholder expectations on concerns as varied as ethical business conduct, labor practices, climate change, responsible use of diminishing natural resources and contribution to socio-economic challenges in their market catchments. These are perspectives and skills that are still glossed over, by academic and professional institutions, as they develop the leaders of the future. Essentially, this book: Articulates the strategic business case for doing good in a good business; the why, and where this trajectory is leading Provides strategies to lead authentically on the array of issues that provide key stakeholders - customers, investors, governments and employees - with a greater reason to engage with and build loyalty to the business Provides strategies to energize and spark innovation among his/her employees in an organization on these issues so that transformative power is harnessed.
Chapter 19 Prove -- Chapter 20 The Board -- Chapter 21 The Executive -- Chapter 22 The Organization -- Chapter 23 Language -- Chapter 24 Habits -- Chapter 25 Disciplines -- Chapter 26 Courage -- Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Organizational change; Leadership; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Management